1998
DOI: 10.1002/(sici)1097-4695(199810)37:1<23::aid-neu3>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell-cell interactions in the developmental regulation of Ca2+-activated K+ currents in vertebrate neurons

Abstract: The functional expression of the Ca2+‐activated K+ current (IK[Ca]) is dependent on cell‐cell interactions in developing chick autonomic neurons. In chick ciliary ganglion (CG) neurons, expression of macroscopic IK[Ca] coincides with the formation of synapses with target tissues. CG neurons that develop in vivo in the absence of normal target tissues fail to express functional IK[Ca], although voltage‐activated Ca2+ currents and most other ionic currents are expressed at normal amplitudes and densities. CG neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
1
18
1
Order By: Relevance
“…Cd 2ϩ (100 M) inhibited spontaneous EPSPs and APs in neurons of two adults, two juveniles, and one neonatal. In contrast to previous reports (Edwards et al 1995;Selyanko 1992) no instances of spontaneous sustained rhythmical action potential discharge, akin to pacemaker-like activity, were recorded. Sustained repetitive discharge could be evoked in some neurons on injection of small depolarizing currents (data not shown).…”
Section: R E S U L T Scontrasting
confidence: 99%
See 2 more Smart Citations
“…Cd 2ϩ (100 M) inhibited spontaneous EPSPs and APs in neurons of two adults, two juveniles, and one neonatal. In contrast to previous reports (Edwards et al 1995;Selyanko 1992) no instances of spontaneous sustained rhythmical action potential discharge, akin to pacemaker-like activity, were recorded. Sustained repetitive discharge could be evoked in some neurons on injection of small depolarizing currents (data not shown).…”
Section: R E S U L T Scontrasting
confidence: 99%
“…ICGs of adult animals contain a heterogeneous population of neurons, identified on the basis of their electrical and synaptic properties (Edwards et al 1995;Selyanko 1992;Selyanko and Skok 1992). However, it is not known when the specification of neuronal subtypes occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of functional K Ca in chick CG neurons depends on trophic factors released from preganglionic nerve terminals and ocular target tissues (16,17). We have previously demonstrated that K Ca are regulated by target-derived TGF␤1/4, which stimulates the development of K Ca (24), and target-derived TGF␤3, which inhibits the development of K Ca (25).…”
Section: Discussionmentioning
confidence: 99%
“…13 and 14), including chick ciliary ganglion (CG) neurons (15). The development of K Ca in chick CG neurons is regulated by interactions with target tissues and preganglionic innervation (16,17). Functional K Ca are not present in CG neurons before synapse formation with target tissues (18) or in later-stage CG neurons that develop in vivo in the absence of either target tissues or preganglionic input (16).…”
mentioning
confidence: 99%